Optimal Dynamic Risk Sharing when Enforcement is a Decision Variable - Thorsten Koeppl (Queen's University, Department of Economics, 2005)
Societies provide institutions that are costly to set up, but able to enforce long-run relationships. We study the optimal decision problem of using self-governance for risk sharing or governance through enforcement provided by these institutions. Third-party enforcement is modelled as a costly technology that consumes resources, but permits the punishment of agents who deviate from ex-ante specified allocations. We show that it is optimal to employ the technology whenever commitment problems prevent first-best risk sharing, but never optimal to provide incentives exclusively via this technology. Commitment problems then persist and the optimal incentive structure changes dynamically over time with third-party enforcement monotonically increasing in the relative inequality between agents.
Keywords: C73; D60; D91; K49; 330; Limited Commitment; Risk Sharing; Third-party Enforcement